INVESTIGATING THE EFFECTIVENESS OF DIFFERENT INHALER DEVICES IN DELIVERING MEDICATION TO PATIENTS WITH OBSTRUCTIVE LUNG DISEASES - Alduwayyikh Ziyad Shujaa, Alshammari Saad Khulaif, Alenezi Bander Abdullah , Alotaibi Adel Aeydh, Alsaif Khalaf Abdulrahman K , Alotaibi Ahmad Bandar, Almutairi Faisal Nawar, Alanazi Salem Mohammed,; Alanazi Muhana Abdulkarem, Alharbi Shaiem Abdullah, Almutairi Fahad Saud, Alrashidi Majed Alfalayah (Chelonian Research Foundation, 2022)
Patients with asthma and COPD experience a significant burden, often leading to recurrent hospitalizations owing to exacerbations. There are many factors contributing to the inadequate disease management in people with asthma and COPD. It is linked to health care providers not following guidelines and patients not properly using inhalers or following treatment plans. This study intends to provide information on inhaler technique and its influence on quality of life (QoL) and symptom management in a standard sample of patients with chronic lung disease from a randomized controlled trial focusing on medication adherence. Chronic obstructive pulmonary disease (COPD) is a significant economic burden and necessitates consistent and continuous therapy. Inhalation therapy is advised for all illness stages to deliver active molecules straight to the target site of action and reduce unwanted side effects. Inhalers are essential for effectively managing people with COPD, and selecting the right one is just as critical as choosing the medication. The primary parameters affecting inhaled medication deposition in the airways are the patient's inhalation flow rate, aerosol velocity, and the size of inhaled drug particles. These factors eventually influence the quantity of medicine that reaches the intended spot, consequently affecting the patient's functional and clinical reactions. Patients' proficiency and knowledge in using inhalers have a direct impact on the effectiveness of the treatment. However, in daily clinical practice, insufficient attention is paid to the characteristics of various inhalers and patients' proficiency in using the device. Clear recommendations are essential to assist healthcare professionals in recommending and prescribing the most suitable inhaled drug/device product. This review attempts to give the most recent research about the significance of the inhaler device in treating individuals with COPD. Key Words: Diabetes, antidiabetic drug, skeleton, bone, bone health